Limonene inhibits Candida albicans growth by inducing apoptosis - Thakre, Archana; Zore, Gajanan; Kodgire, Santosh; Kazi, Rubina; Mulange, Shradha; Patil, Rajendra; Shelar, Amruta; Santhakumari, Bayitigeri; Kulkarni, Mahesh J.; Kharat, Kiran; Karuppayil, Sankunny Mohan (Medical Mycology, 2018)
Anti-Candida potential of limonene was evaluated against planktonic growth, biofilm (adhesion, development and maturation) and morphogenesis of Candida albicans in this study. Limonene is a major constituent of citrus oil and most frequently used terpene in food and beverage industry due to its pleasant fragrance, nontoxic, and is generally recognized as safe (GRAS) flavoring agent as well as treatment option in many gastrointestinal diseases. Limonene exhibited excellent anti-Candida activity and was equally effective against planktonic growth of C. albicans isolates differentially susceptible to FLC (N = 35). Limonene inhibited morphogenesis significantly at low concentration. However, it showed stage dependent activity against biofilm formation, that is, it was more effective against adhesion followed by development and maturation. Limonene also exhibited excellent synergy with FLC against planktonic and biofilm growth. SWATH-MS analysis led to identification of limonene responsive proteins that provided molecular insight of its anti-Candida activity. Proteomic analysis revealed upregulation of proteins involved in cell wall glucan synthesis (Kre6); oxidative stress (Rhr2, Adh7 and Ebp1); DNA damage stress (Mbf1 and Npl3); nucleolar stress (Rpl11, Rpl7, Rpl29, Rpl15) and down regulation of cytoskeleton organization (Crn1, Pin3, Cct8, Rbl2), and so forth, in response to limonene. Limonene mediated down regulation of Tps3 indicates activation of caspase (CaMca1) and induction of apoptosis in C. albicans. These results suggest that limonene inhibits C. albicans growth by cell wall/membrane damage induced oxidative stress that leads to DNA damage resulting into modulation of cell cycle and induction of apoptosis through nucleolar stress and metacaspase dependent pathway.

Oxidative stress induced by piperine leads to apoptosis in Candida albicans - Thakre, Archana; Jadhav, Vyankatesh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan; Karuppayil, S. Mohan (Medical Mycology, 2021)
Candida albicans is a member of pathogens with potential drug resistance threat that needs novel chemotherapeutic strategies. Considering the multifarious biological activities including bioenhancer activity, anti-Candida potential of piperine was evaluated against planktonic/biofilm and hyphal growth of C. albicans alone or in combination as a synergistic agent with fluconazole. Piperine inhibits planktonic growth at or less than 15 mu g/ml, hyphae induction at 5 mu g/ml concentration, and exhibits stage-dependent activity against biofilm growth of a fluconazole-resistant strain of C. albicans (ATCC10231). Though piperine couldn't kill inoculum completely at minimum inhibitory concentration (MIC), it is fungicidal at higher concentrations, as shown in apoptosis assay. FIC index values indicate that piperine exhibits excellent synergistic activity with fluconazole against planktonic (0.123) and biofilm (0.215) growth of an FLC resistant strain. Mode of anti-Candida activity was studied by identifying piperine responsive proteins wherein the abundance of 25 proteins involved in stress response, signal transduction and cell cycle were modulated (22 up and 3 downregulated) significantly in response to piperine (MIC50). Modulation of the proteins involved suggests that piperine affectsmembrane integrity leading to oxidative stress followed by cell cycle arrest and apoptosis in C. albicans. Flow cytometry-basedmitochondrialmembrane potential (MMP), cell cycle and apoptosis assay, as well as real-time quantitative polymerase chain reaction analysis of selected genes, confirms piperine induced oxidative stress (TRR1), cell cycle arrest and apoptosis (CaMCA1). Based on our results, we conclude that piperine inhibits planktonic and difficult-to treat-biofilm growth of C. albicans by affecting membrane integrity thereby inducing oxidative stress and apoptosis. Lay Abstract Piperine inhibit Candida albicans growth (planktonic and biofilm) significantly in our study. Piperine exhibits excellent synergistic potential with fluconazole The proteome analysis suggests that piperine induced membrane damage leads to oxidative stress followed by cell cycle arrest and apoptosis.
Keywords: Apoptosis; C. albicans; drug resistance; piperine; proteomics; synergy

Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics